Are midwifery students ready for interprofessional education with project-based learning? - Ari Indra Susanti; Ariyati Mandiri; Lani Gumilang (Himpunan Pengembang Kurikulum Indonesia, 2025)
Patient-centered health services require preparation for Interprofessional Collaboration (IPC). Therefore, it is essential to equip health worker students with Interprofessional Education (IPE) training. This study aims to determine the readiness of midwifery students to implement Interprofessional Education (IPE) using a Project-Based Learning (PjBL) approach. A descriptive research method with a cross-sectional design was conducted at the Midwifery Study Program, Faculty of Medicine, Universitas Padjadjaran. Data collection was performed using questionnaires administered to 30 students (7th semester) before the start of PjBL, who collaborated with nursing students in the Undergraduate Nursing Study Program at Universitas Padjadjaran. Descriptive data analysis with frequency and percentage statistical tests. The study's results showed that midwifery students were highly receptive to IPE learning, which involves working together to solve patient problems, benefiting from learning related to professional limitations, communication skills, teamwork skills, and collaboration in small group settings. Additionally, most midwifery students can participate in IPE by achieving a score of 79.50-100. This study concludes that student readiness can support the achievement of PjBL-based IPE learning objectives. Abstrak Pelayanan kesehatan yang berpusat pada pasien perlu dipersiapkan Interprofessional Collaboration (IPC), maka perlu membekali mahasiswa tenaga kesehatan dengan pembelajaran Interprofessional Education (IPE). Penelitian ini bertujuan mengetahui kesiapan mahasiswa kebidanan melaksanakan IPE berbasis Project-Based Learning (PjBL). Metode penelitian deskriptif dengan cross sectional yang dilakukan di Program Studi Kebidanan Fakultas Kedokteran Universitas Padjdajaran. Pengumpulan data menggunakan kuesioner yang diberikan kepada 30 mahasiswa (semester 7) sebelum dimulai PjBL yang berkolaborasi dengan mahasiswa keperawatan di Program Studi Sarjana Keperawatan Universitas Padjadjaran. Analisis data deskriptif dengan uji statistik frekuensi dan persentase. Hasil penelitian didapatkan mahasiswa kebidanan sangat siap dalam pembelajaran IPE yang bertujuan untuk bekerja sama untuk memecahkan masalah pasien, manfaat pembelajaran terkait keterbatasan profesional, keterampilan komunikasi, keterampilan kerja tim, dan kolaborasi dalam pembelajaran kelompok kecil. Selain itu, sebagian besar mahasiswa kebidanan dapat melakukan IPE dengan mendapatkan nilai 79.50-100. Simpulan penelitian ini, kesiapan mahasiswa dapat mendukung tercapainya tujuan pembelajaran IPE berbasis PjBL. Kata Kunci: interprofessional education; kesiapan mahasiswa; pembelajaran berbasis proyek